MEKATA: A Practical and Appropriate Word Affix Media Application for Phase B Morphology Learning - Rani Setiawaty; Petriyanti Tesya Putri; Meiva Khoryati; Sri Mulyani (Jurnal Prajaiswara, 2026)
Introduction/Main Objectives: This study aims to develop and test the feasibility and practicality of MEKATA (Exploring the World of Words and Affixes) as an innovative digital-based learning media to improve the ability to use affixes in words and sentences by students in grades III and IV of elementary school. Novelty: MEKATA offers innovation in the form of integrating regional culture into learning the use of Android-based word affixes. This integration makes learning more contextual, more meaningful and plays a role in developing the character and cultural understanding of elementary school students. Research Methods: This study uses the Research and Development (R&D) method with the ADDIE model which consists of stages of analysis, design, development, implementation and evaluation. The feasibility test was carried out by material experts and media experts, while the practicality test was obtained through teacher and student responses after using the MEKATA application. Finding/Results: The validation results show that MEKATA is declared very feasible based on the assessment of media experts by 87.7% and material experts by 81.4%. Meanwhile, practicality test results showed that the application was categorized as very practical, with 89.5% of teachers and 100% of students rating it. The application was deemed engaging, easy to use, and relevant to Javanese cultural context and regional heritage.